Multiple intelligences mapping for tutors in Universitas Terbuka - Mery Berlian; Iqbal Miftakhul Mujtahid; Rian Vebrianto; Musa Thahir (Jurnal Cakrawala Pendidikan, 2022)
This study aimed to map and to develop Multiple Intelligences for basic education tutors in Universitas Terbuka. This study was a survey research with a sample of 193 tutors consisted of 101 men (52.33%) and 92 women (47.67%). The instrument used was the Multiple Intelligences Survey consisted of nine constructs with an average alpha croanbach value of 0.859 with high criteria. The results of the study showed that there were no significant differences in multiple intelligence based on gender, work base, number of institutions, age, length of service, and ethnicity. The study also showed that there were significant relationships between physical/kinesthetic, existential/spiritual, interpersonal, intrapersonal, logical/mathematical thinking, musical/rhythmic, naturalistic, verbal/linguistic, and visual/spatial. Judging from the value of the correlation coefficient, kinesthetic intelligence and interpersonal intelligence have the highest value of 0.881. This research could be used to develop the human resources of educators, especially Tutors, in increasing their multiple intelligences for universities and the government. This study suggested the importance of increasing the multiple intelligences of tutors or educators in the the management in universities or the government. For this reason, educational institutions already have educators with good interpersonal and intrapersonal intelligence, and feel the need to increase the intelligence in the aspect of naturalistic intelligence, for example, by conducting family gathering events that interact directly with the nature. This study is different with the previous studies with a similar theme regarding the research sample. This research produced valuable policy recommendations for the management at Universitas Terbuka and the government to do the mapping and how to increase the multiple intelligences of educators to be ready to face the challenges and opportunities. On the other hand, illustrates that men and women have the same opportunity in mastering this multiple intelligences